Trastorno negativista desafiante y su incidencia en las relaciones escolares - Vaca Bravo, Debora Mariana (2020)
The purpose of this case study was to identify the event of the defiant negativist disorder in the school relations of an 8-year-old child. This disorder deals with disruptive behaviors, which causes problems with their peers, teachers and therefore does not comply with orders. To obtain the diagnosis of the challenging negativist disorder, resources such as: the semi-structured interview, observation sheet, psychometric tests and the diagnostic criteria of the DSM-5 were used. A psychotherapeutic plan based on cognitive behavioral therapy was designed which helped to improve their school relationships that have brought them inconveniences since their entire school stage, which have marked their personality and training towards adolescence and adulthood, what is intended to be improved from at an early age.